Determinan Pengelolaan Keuangan Mahasiswa STIE Surakarta - Adelia Mega Hutami; Astuning Saharsini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The objective of this research is to examine the influence of financial literacy, income, self-control, and lifestyle on the financial management of STIE Surakarta students. The study was conducted at the Surakarta School of Economics, utilizing primary data with a population of 2,568 active students. The sample size for this research was determined using the Slovin formula, resulting in 92 respondents. The research employed methods such as instrument data test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results indicate that all independent variables in this study collectively influence financial management. In the t-test of this study, the financial literacy and self-control variables partially have a positive and significant impact on student financial management, while the income and lifestyle variables partially have a negative and non-significant impact on student financial management.